2016
DOI: 10.18176/jiaci.0051
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Low-Molecular-Weight Mast Cell–Activating Factors in Serum From Patients With Chronic Spontaneous Urticaria

Abstract: Background: Functionally active autoantibodies to IgE and to the high-affinity IgE receptor (FcεRI) can be detected in serum in about 40% of patients with chronic spontaneous urticaria (CSU). Recent studies showed that serum from patients with CSU can induce activation of mast cells, irrespective of whether they carry high-affinity IgE receptors. Objective: To evaluate mast cell activation induced by factors in the serum of CSU patients with a molecular weight lower than that of autoantibodies. Methods: Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…This fact suggests a pathomechanism that bypasses the IgE receptor mechanism. In subsequent studies, we showed that low-molecular-weight circulating factors (molecular weight about 30 kDa) may be involved in the activation of mast cells in chronic urticaria patients 41 , thus confirming very old data by Grattan and co-workers 42 .…”
Section: Established Factssupporting
confidence: 87%
“…This fact suggests a pathomechanism that bypasses the IgE receptor mechanism. In subsequent studies, we showed that low-molecular-weight circulating factors (molecular weight about 30 kDa) may be involved in the activation of mast cells in chronic urticaria patients 41 , thus confirming very old data by Grattan and co-workers 42 .…”
Section: Established Factssupporting
confidence: 87%
“…This brings various histamine releasing factors to the blood, such as activated coagulation factors to activate protease activating receptor (PAR) on mast cells, autoantibodies against IgE or the high affinity IgE receptor (FcεRI) and autoantigens for IgE to the tissue. These factors should induce further release of histamine from mast cells in the vicinity, as well as neuropeptides released from free nerve endings in the skin by histamine [20,[30][31][32][33][34][35]. On the other hand, the expression of tissue factor on endothelial cells and histamine release from mast cells are consequentially suppressed by adenosine derived from ATP which is released from mast cells together with histamine [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the increase of the intrinsic coagulation potential in CSU,3 the activation of factor X and II in the common pathway of coagulation, and the induction of vascular endothelial cell gap formation by these factors may be further enhanced in CSU.Autoantibodies against IgE or its receptor (FcɛRI) on mast cellsare known to be involved in the pathogenesis of CSU. Moreover, the presence of histamine-releasing factors has also been reported in the plasma of patients with CSU 7,8. We presume that plasma leakage caused by the activation of the coagulation cascade triggered by TF expressed on either endothelial cells or monocytes allows these factors to move out to the extravascular space and encounter dermal mast cells, which then degranulate and cause massive vascular hyperpermeability and wheal formation.…”
mentioning
confidence: 69%